231k views
5 votes
Add: (3x2 - 5x + 6) + (9 - 8x - 4x2)

A)
12x2 - 13x + 2


B)
7x2 + 3x - 3


C)
7x2 - 13x + 15


D)
-x2 - 3x + 15


E)
-x2 - 13x + 15

2 Answers

3 votes

Answer:
E) -x^2-13x+15 .

Explanation:

To add :
(3x^2 - 5x + 6) + (9 - 8x - 4x^2)


=3x^2 - 5x + 6+ 9 - 8x - 4x^2

This can be re-written as :


3x^2-4x^2-5x-8x+6+9

Combine like terms as


=(3-4)x^2-(5+8)x+15\ \ [\because (-)(+)=(-)]\\\\=-x^2-13x+15

Therefore,
(3x^2 - 5x + 6) + (9 - 8x - 4x^2)=-x^2-13x+15

Hence, the correct option is
E) -x^2-13x+15 .

User Ryan Sperzel
by
6.4k points
3 votes
Add: (3x2 - 5x + 6) + (9 - 8x - 4x2)
The givens should be arranged first before we can start answering.
3x2 - 5x + 6 plus
-4x2 - 8x + 9
= -x2 - 13x +15
Therefore, the answer to the question is E) -x2 - 13x +15

User Steven Ventimiglia
by
7.1k points